Systematic Review of Tissue-Engineered Vascular Grafts - Durán-Rey, David; Crisóstomo, Verónica; Sánchez-Margallo, Juan A.; Sánchez-Margallo, Francisco M. (Frontiers in Bioengineering and Biotechnology, 2021)
Pathologies related to the cardiovascular system are the leading causes of death worldwide. One of the main treatments is conventional surgery with autologous transplants. Although donor grafts are often unavailable, tissue-engineered vascular grafts (TEVGs) show promise for clinical treatments. A systematic review of the recent scientific literature was performed using PubMed (Medline) and Web of Science databases to provide an overview of the state-of-the-art in TEVG development. The use of TEVG in human patients remains quite restricted owing to the presence of vascular stenosis, existence of thrombi, and poor graft patency. A total of 92 original articles involving human patients and animal models were analyzed. A meta-analysis of the influence of the vascular graft diameter on the occurrence of thrombosis and graft patency was performed for the different models analyzed. Although there is no ideal animal model for TEVG research, the murine model is the most extensively used. Hybrid grafting, electrospinning, and cell seeding are currently the most promising technologies. The results showed that there is a tendency for thrombosis and non-patency in small-diameter grafts. TEVGs are under constant development, and research is oriented towards the search for safe devices.